PENGEMBANGAN KALEIDOSKOP BERBASIS FLIPBOOK DIGITAL PEMERINTAH KABUPATEN SUKABUMI TAHUN 2025 - Kamila Futri H; Bayu Suriatmaja Suwanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital media has encouraged the Sukabumi Regency Government to utilize digital platforms as a medium for disseminating public information. Through the Department of Communication, Informatics, and Encryption of Sukabumi Regency, the Sukabumi Regency Government actively publishes various governmental activities, programs, and regional achievements on social media. This study aims to develop a digital flipbook-based kaleidoscope as a medium for documenting and publishing information related to the Sukabumi Regency Government in 2025. The study employed a qualitative descriptive approach, with data collected through observation, documentation, and active participation at the Department of Communication, Informatics, and Encryption of Sukabumi Regency. The media development process applied the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The results indicate that the flipbook-based digital kaleidoscope is capable of presenting governmental information in a more structured, attractive, and accessible manner across various digital devices. In addition, the implementation of consistent visual design and interactive flipbook features supports information readability and strengthens the visual identity of the Sukabumi Regency Government.